2013
DOI: 10.1016/j.bmcl.2013.06.096
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antifungal activities of miltefosine analogs

Abstract: Miltefosine is an alkylphosphocholine that shows broad-spectrum in vitro antifungal activities and limited in vivo efficacy in mouse models of cryptococcosis. To further explore the potential of this class of compounds for the treatment of systemic mycoses, nine analogs (3a–3i) were synthesized by modifying the choline structural moiety and the alkyl chain length of miltefosine. In vitro testing of these compounds against the opportunistic fungal pathogens Candida albicans, Candida glabrata, Candida krusei, As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
(29 reference statements)
3
18
0
1
Order By: Relevance
“…A larger spectrum of MIC values (0.5-4 mg ml 21 ) was reported by Brilhante et al (2014) for the treatment of the mycelial form of S. brasiliensis. The MIC values for miltefosine reported here are in line with the 2 mg ml 21 value reported for the treatment of Candida albicans, Candida glabrata, Candida krusei, Crytococcus gatti, Crytococcus neoformans, Aspergillus fumigatus and Trichophyton mentagrophytes with this drug (Widmer et al, 2006;Tong et al, 2007;Ravu et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A larger spectrum of MIC values (0.5-4 mg ml 21 ) was reported by Brilhante et al (2014) for the treatment of the mycelial form of S. brasiliensis. The MIC values for miltefosine reported here are in line with the 2 mg ml 21 value reported for the treatment of Candida albicans, Candida glabrata, Candida krusei, Crytococcus gatti, Crytococcus neoformans, Aspergillus fumigatus and Trichophyton mentagrophytes with this drug (Widmer et al, 2006;Tong et al, 2007;Ravu et al, 2013).…”
Section: Discussionsupporting
confidence: 88%
“…and Aspergillus sp. (Widmer et al, 2006;Ravu et al, 2013), and also for the mycelial form of S. schenckii complex species (Brilhante et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, Wiederhold et al found that, for cryptococcal meningitis and disseminated cryptococcosis models, doses up to 45 mg/kg/day of miltefosine did not improve the survival or reduce the infectious process (48). Similarly, intraperitoneal treatment with doses up to 10 mg/kg/day of miltefosine was not effective in a murine model of disseminated candidiasis (49). These negative results may be associated with the high binding of miltefosine to plasma proteins (up to 95%) (25), reducing their systemic activity and its penetration across the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Miltefosine has been used successfully in a combination therapy with voriconazole and terbinafine against Scedosporium prolificans (13) and in a case of S. prolificans mediastinitis (14). In animal models against disseminated cryptococcosis or candidiasis, some authors found that miltefosine was effective (9), whereas others reported that it provided only limited effectiveness (15,16). The drug's potential effect against molds, either alone or in combination, has not yet been tested.…”
mentioning
confidence: 99%